1987
DOI: 10.1021/bk-1987-0344.ch024
|View full text |Cite
|
Sign up to set email alerts
|

Axial Coordination in Nickel and Vanadium Porphyrins: Transient and Difference Raman Spectroscopy

Abstract: Nickel-and vanadium-porphyrin complexes and Ni(II)-reconstituted hemoglobin ( Ni Hb) and myoglobin ( Ni Mb) have been investigated using cw and transient resonance Raman spectroscopy.The state of axial coordination at the metal in these materials can be determined using the characteristic frequencies of the Raman marker lines arising from the porphyrin moiety.The state of axial ligation is highly sensitive to the molecular environment of these geoporphyrin analogs.Whether vanadium porphyrins are 5-or 6-coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The prospect ligand must be capable of penetrating the microwell created by the elevated vanadium atom in order to create the coordinating bond. Shelnutt et al observed similar tendencies and found that pyrrolidine coordinated much more readily with VOOEP than did pyridine, and this coordination caused a red shift in the Soret band from 407 to 425 nm.…”
Section: To Be or Not To Be (A Porphyrin)that Is The Question The Ch...mentioning
confidence: 78%
“…The prospect ligand must be capable of penetrating the microwell created by the elevated vanadium atom in order to create the coordinating bond. Shelnutt et al observed similar tendencies and found that pyrrolidine coordinated much more readily with VOOEP than did pyridine, and this coordination caused a red shift in the Soret band from 407 to 425 nm.…”
Section: To Be or Not To Be (A Porphyrin)that Is The Question The Ch...mentioning
confidence: 78%